PRESSER MECHANISMS IN ADRIAMYCIN-INDUCED NEPHROPATHY WITH HYPERTENSION IN RATS - Franco, R.; Gut, Ana Lúcia [UNESP]; Ferrarispadotto, A.; Georgette, J.; GAVRAS, I; Gavras, H. (Amer Heart Assoc, 1994)
We explored the role of angiotensin II and vasopressin in the maintenance of blood pressure during the nephrotic syndrome of adriamycin-induced nephropathy in rats. All 91 rats treated with adriamycin developed chronic renal failure with nephrotic syndrome, which was more pronounced in the normotensive rats than the 35% who became hypertensive. Angiotensin II blockade with DuP 753 produced a significantly greater hypotensive response in both the adriamycin-hypertensive (-16+/-3 mmHg) and adriamycin-normotensive (-14+/-5 mmHg) groups than the saline-treated controls (-5+/-1 mm Hg, P<.05). Vasopressin blockade with either a V1V2 inhibitor or a selective V-1 inhibitor produced a hypotensive response in adriamycin-hypertensive rats only (by -16+/-4 and -17+/-2 mm Hg, respectively, P<.01), although the nonselective vasopressin inhibitor produced similar fluid loss and body weight reduction in all three groups. The data suggest that in adriamycin-induced nephropathy with nephrotic syndrome, angiotensin II contributes to blood pressure maintenance in both hypertensive and normotensive animals, whereas the presser action of vasopressin contributes to elevated blood pressure in hypertensive animals only.
Keywords: DOXORUBICIN; RECEPTORS, VASOPRESSIN; ANGIOTENSIN II; KIDNEY FAILURE